Positive electrode composition, coating liquid for forming a positive electrode and method for manufacturing the same, positive electrode and method for manufacturing the same, and battery and method for manufacturing the same
Patent Information
- Application Number
- JP2025059936
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0009】 本開示によれば、サイクル特性に優れた電池を実現可能な正極組成物が提供される。また、本開示によれば、サイクル特性に優れた電池を実現可能な正極形成用塗液が提供される。また、本開示によれば、サイクル特性に優れた電池を実現可能な正極が提供される。また、本開示によれば、サイクル特性に優れた電池が提供される。更に、本開示によれば、上記正極形成用塗液を容易に製造可能な正極形成用塗液の製造方法、上記正極を容易に製造可能な正極の製造方法、及び、上記電池を容易に製造可能な電池の製造方法が提供される。
Smart Images

Figure 2026166766000001
Abstract
Description
[Technical Field]
[0001] This disclosure relates to a positive electrode composition, a coating liquid for forming a positive electrode and a method for manufacturing the same, a positive electrode and a method for manufacturing the same, and a battery and a method for manufacturing the same. [Background technology]
[0002] Due to the growing environmental and energy concerns, there is a surge in the development of technologies aimed at realizing a low-carbon society that reduces reliance on fossil fuels. Such technological developments are diverse and include the development of low-emission vehicles such as hybrid electric vehicles and electric vehicles, the development of renewable energy power generation and storage systems such as solar and wind power generation, and the development of next-generation power grids that efficiently supply electricity and reduce transmission losses.
[0003] One of the key devices required for these technologies is the battery, and such batteries need high energy density to miniaturize the system. They also need high output characteristics to enable stable power supply regardless of ambient temperature. Furthermore, they need good cycle characteristics to withstand long-term use. For these reasons, there is a rapid shift from conventional lead-acid batteries, nickel-cadmium batteries, and nickel-metal hydride batteries to lithium-ion secondary batteries, which have higher energy density, output characteristics, and cycle characteristics.
[0004] Conventionally, the positive electrode of a lithium-ion secondary battery is manufactured by coating a current collector with a positive electrode paste containing a positive electrode active material, a conductive material, and a binder. Lithium-containing composite oxides such as lithium cobalt oxide and lithium manganese oxide have been used as the positive electrode active material. Furthermore, because positive electrode active materials have poor conductivity, conductive materials such as carbon black have been added to the positive electrode paste to impart conductivity (for example, Patent Document 1). [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2008-227481 [Overview of the Initiative] [Problems that the invention aims to solve]
[0006] In recent years, there has been a growing demand for further performance improvements in batteries such as lithium-ion rechargeable batteries.
[0007] One of the purposes of this disclosure is to provide a positive electrode composition that enables the realization of a battery with excellent cycle characteristics. Another purpose of this disclosure is to provide a coating liquid for forming a positive electrode that enables the realization of a battery with excellent cycle characteristics. Another purpose of this disclosure is to provide a positive electrode that enables the realization of a battery with excellent cycle characteristics. Another purpose of this disclosure is to provide a battery with excellent cycle characteristics. Furthermore, one of the purposes of this disclosure is to provide a method for manufacturing a coating liquid for forming a positive electrode that can be easily manufactured, a method for manufacturing a positive electrode that can be easily manufactured, and a method for manufacturing a battery that can be easily manufactured. [Means for solving the problem]
[0008] This disclosure relates, for example, to the following [1] to
[10] . [1] It comprises an active material, a binder, and a conductive material. The conductive material contains carbon black and carbon nanotubes, A positive electrode composition in which the average length of the carbon nanotubes is 0.4 μm or more and 8 μm or less. [2] The cathode composition according to [1], wherein the average diameter of the carbon nanotubes is 1 nm or more and 15 nm or less. [3] The positive electrode composition according to [1] or [2], wherein the carbon nanotube content is 10% by mass or more and 70% by mass or less based on the total amount of the conductive material. [4] A positive electrode comprising a composite layer consisting of any one of the positive electrode compositions described in [1] to [3]. [5] A battery comprising the positive electrode according to claim 4. [6] A coating liquid for forming a positive electrode, comprising an active material, a binder, a conductive material, and a liquid medium, wherein the conductive material contains carbon black and carbon nanotubes, and the carbon nanotubes have an average length of 0.4 μm or more and 8 μm or less. [7] A method for producing a coating liquid for forming a positive electrode, comprising: a first step of mixing carbon nanotube powder with a liquid medium to obtain a first slurry containing carbon nanotubes; a second step of mixing carbon black, a binder, an active material and a liquid medium to obtain a mixed liquid; and a third step of mixing the first slurry with the mixed liquid to obtain a coating liquid for forming a positive electrode containing the carbon nanotubes, the carbon black, the binder, the active material and the liquid medium, , wherein the first step is a step of mixing the carbon nanotube powder and the liquid medium such that the average length of the carbon nanotubes in the first slurry is 0.4 μm or more and 8 μm or less. [8] The production method according to claim 7, wherein the second step is a step of mixing the second slurry containing the carbon black, the binder solution containing the binder, and the active material. [9] A method for producing a positive electrode, comprising a mixture layer forming step of applying the coating liquid for forming a positive electrode according to claim 6 or the coating liquid for forming a positive electrode produced by the production method according to claim 7 onto a current collector to form a mixture layer on the current collector.
[10] A method for producing a battery, comprising: a mixture layer forming step of applying the coating liquid for forming a positive electrode according to claim 6 or the coating liquid for forming a positive electrode produced by the production method according to claim 7 onto a current collector to form a mixture layer on the current collector; and a battery forming step of laminating the positive electrode and the negative electrode with a separator interposed therebetween to obtain a battery. , Effects of the Invention
[0009] This disclosure provides a positive electrode composition that enables the realization of a battery with excellent cycle characteristics. This disclosure also provides a coating liquid for forming a positive electrode that enables the realization of a battery with excellent cycle characteristics. This disclosure also provides a positive electrode that enables the realization of a battery with excellent cycle characteristics. This disclosure also provides a battery with excellent cycle characteristics. Furthermore, this disclosure provides a method for manufacturing a coating liquid for forming a positive electrode that can be easily manufactured, a method for manufacturing a positive electrode that can be easily manufactured, and a method for manufacturing a battery that can be easily manufactured. [Modes for carrying out the invention]
[0010] Preferred embodiments of this disclosure will be described in detail below. In this specification, carbon black may be abbreviated as "CB" and carbon nanotube as "CNT". In this specification, the tilde symbol "~" is used to indicate a numerical range including the numbers before and after it. Specifically, "X~Y" (where X and Y are both numerical values) indicates "X or greater and Y or less".
[0011] (Positive electrode composition) The positive electrode composition of this embodiment comprises an active material, a binder, and a conductive material. The conductive material contains carbon black and carbon nanotubes, with an average length of 0.4 μm to 8 μm.
[0012] The positive electrode composition of this embodiment may be a material that constitutes the composite layer in the positive electrode. By using a positive electrode that constitutes the composite layer made of the positive electrode composition of this embodiment, a battery with excellent cycle characteristics can be realized.
[0013] The basic role of conductive materials is to impart conductivity to active materials that have poor conductivity. In addition, in lithium-ion secondary batteries, the active materials expand and contract due to repeated charging and discharging, causing the contact points between the active materials to gradually be lost. Conductive materials also play a role in connecting the active materials that have lost their contact points, preventing the loss of conductivity.
[0014] The positive electrode composition of this embodiment combines carbon nanotubes having a fibrous structure with carbon black having a granular structure. This combination is thought to improve the ability of the positive electrode composition of this embodiment to follow the expansion and contraction of the active material during battery charging and discharging. Furthermore, the carbon nanotubes in the positive electrode composition of this embodiment have a specific average length. This further improves the aforementioned ability to follow the expansion and contraction, and suppresses performance degradation due to entanglement and aggregation of carbon nanotubes. For these reasons, in this embodiment, the conductive network in the positive electrode is more easily maintained even after repeated charging and discharging of the battery, and it is thought that a battery with excellent cycle characteristics can be realized.
[0015] The components of the positive electrode composition of this embodiment will be described in detail below.
[0016] <Conductive material> The positive electrode composition of this embodiment includes carbon black and carbon nanotubes as conductive materials.
[0017] The average length of the carbon nanotubes is between 0.4 μm and 8 μm. If the average length of the carbon nanotubes is less than 0.4 μm, the ability to follow the expansion and contraction of the active material during battery charging and discharging decreases, resulting in reduced cycle performance. If the average length of the carbon nanotubes is 8 μm or more, the carbon nanotubes tend to aggregate, which can lead to uneven distribution of the carbon nanotubes, increasing internal resistance, and reducing the ability to follow the expansion and contraction of the active material during battery charging and discharging, thus reducing cycle performance. In this embodiment, since the average length of the carbon nanotubes is within the above range, a battery with sufficiently low internal resistance and excellent cycle performance is realized.
[0018] The carbon nanotube may be a single-walled carbon nanotube (SWCNT), a double-walled carbon nanotube (DWCNT), or a multi-walled carbon black (MWCNT). A single-walled carbon nanotube may be a carbon nanotube having a tubular structure made of graphene sheets, a double-walled carbon nanotube may be a carbon nanotube having a structure in which two layers of graphene sheets are stacked in a coaxial tube, and a multi-walled carbon nanotube may be a carbon nanotube having a structure in which three or more layers of graphene sheets are stacked on a coaxial tube.
[0019] The average length of the carbon nanotubes is 0.4 μm or more, and from the viewpoint of obtaining the above-mentioned effects more significantly, it may be 0.5 μm or more, 0.7 μm or more, or 0.9 μm or more. Alternatively, the average length of the carbon nanotubes is 8 μm or less, and from the viewpoint of obtaining the above-mentioned effects more significantly, it may be 6 μm or less, 5 μm or less, or 4 μm or less.
[0020] In this specification, the average length of carbon nanotubes is measured by the following method. The average length of carbon nanotubes is calculated based on images obtained by observing them with a scanning electron microscope (SEM). Specifically, using a field emission scanning electron microscope Regulus8220 (manufactured by Hitachi High-Tech Corporation), 10 images of carbon nanotubes are taken at a magnification of 20,000x. The lengths of 100 randomly selected carbon nanotubes from the resulting images are measured by image analysis, and the average length is obtained by arithmetic mean.
[0021] The average diameter of the carbon nanotubes may be, for example, 1 nm or more, and from the viewpoint of facilitating the development of a conductive network in the positive electrode, it may be 2 nm or more, 3 nm or more, or 4 nm or more. Alternatively, the average diameter of the carbon nanotubes may be, for example, 15 nm or less, and from the viewpoint of facilitating the development of a conductive network in the positive electrode, it may be 12 nm or less, 11 nm or less, 10 nm or less, 9 nm or less, or 8 nm or less.
[0022] In this specification, the average diameter of a carbon nanotube refers to the average diameter measured based on images obtained by observing carbon nanotubes with a transmission electron microscope (TEM). Specifically, it is obtained by using a JEM-2000FX transmission electron microscope (manufactured by JEOL Ltd.), taking 10 images of carbon nanotubes at a magnification of 200,000x, measuring the diameters of 100 randomly selected carbon nanotubes from the obtained images by image analysis, and then taking the arithmetic mean.
[0023] In carbon nanotubes, the peak ratio of the D-band to the G-band in the Raman spectrum (D / G) can be used as an indicator to evaluate the crystallinity of the carbon nanotube. The peak ratio (D / G) of carbon nanotubes may be, for example, 0.1 or higher, and from the viewpoint of further improving conductivity, it may be 0.2 or higher, 0.3 or higher, 0.4 or higher, 0.5 or higher, or 0.6 or higher. Alternatively, the peak ratio (D / G) of carbon nanotubes may be, for example, 1.5 or lower, and from the viewpoint of further improving conductivity, it may be 1.4 or lower, 1.3 or lower, 1.2 or lower, 1.1 or lower, 1.0 or lower, or 0.9 or lower.
[0024] In this specification, Raman spectra are defined as the Raman spectra of carbon nanotubes measured using a micro-laser Raman system (Thermo Fisher Scientific, product name "Nicolet Almega XR"), and include the G band (1600 cm⁻¹). -1 (Nearby) and D-band (1350cm) -1 A vibrational mode called the G band is observed. The G band is a vibrational mode originating from the hexagonal lattice structure of graphite, which is the cylindrical surface of the carbon nanotube, and the D band is a vibrational mode originating from the amorphous region. The lower the peak intensity ratio of the D band to the G band (D / G ratio), the more crystalline the carbon nanotube can be considered to be.
[0025] The carbon nanotubes may be, for example, those produced using a commercially available product. The carbon nanotubes may be, for example, a commercially available carbon nanotube adjusted such that the average length falls within the above range.
[0026] The carbon black may be selected, for example, from the group consisting of acetylene black, furnace black and Ketjen black, and is preferably acetylene black.
[0027] The BET specific surface area of the carbon black may be, for example, 100 m 2 / g or more, and may be 110 m 2 / g or more, 120 m 2 / g or more, or 130 m 2 / g or more. This tends to further develop the conductive network formed in the positive electrode. The BET specific surface area of the carbon black may be, for example, 900 m 2 / g or less, and may be 890 m 2 / g or less, 880 m 2 / g or less, or 870 m 2 / g or less. This tends to further develop the conductive network formed in the positive electrode.
[0028] In the present specification, the BET specific surface area of carbon black is a value measured by a static volumetric method in accordance with JIS Z8830 using nitrogen as an adsorbate.
[0029] The average primary particle diameter of the carbon black may be, for example, 10 nm or more, and from the viewpoint of reducing the interparticle interaction between carbon black particles and facilitating obtaining better dispersibility, it may be 12 nm or more, 14 nm or more, or 16 nm or more. In addition, the average primary particle diameter of the carbon black may be, for example, 30 nm or less, and from the viewpoint of increasing the number of conductive paths to the active material and facilitating obtaining higher battery characteristics, it may be 27 nm or less, 24 nm or less, or 22 nm or less.
[0030] In this specification, the average primary particle diameter of carbon black can be determined by measuring the primary particle diameter of 100 or more carbon black particles randomly selected from transmission electron microscope (TEM) images magnified 50,000 times, and calculating the average value. Primary particles of carbon black have a small aspect ratio and a shape close to a perfect sphere, but they are not perfectly spherical. Therefore, in this specification, the primary particle diameter of carbon black is defined as the largest line segment connecting two points on the outer circumference of the primary particle in the TEM image.
[0031] The carbon nanotube content in the conductive material may be, for example, 5% by mass or more based on the total amount of the conductive material, and may be 10% by mass or more, 15% by mass or more, 18% by mass or more, or 20% by mass or more, from the viewpoint of obtaining the above-mentioned effects more significantly. Alternatively, the carbon nanotube content may be, for example, 70% by mass or less based on the total amount of the conductive material, and may be 60% by mass or less, 50% by mass or less, or 40% by mass or less, from the viewpoint of obtaining the above-mentioned effects more significantly.
[0032] The carbon black content in the conductive material may be, for example, 30% by mass or more based on the total amount of the conductive material, and may be 40% by mass or more, 50% by mass or more, or 60% by mass or more from the viewpoint of obtaining the above-mentioned effects more significantly. Alternatively, the carbon black content in the conductive material may be, for example, 95% by mass or less based on the total amount of the conductive material, and may be 90% by mass or less, 85% by mass or less, 82% by mass or less, or 80% by mass or less from the viewpoint of obtaining the above-mentioned effects more significantly.
[0033] The positive electrode composition of this embodiment may further contain other components besides carbon nanotubes and carbon black as conductive materials. Examples of other components include graphene, graphite, porous carbon, and the like.
[0034] The content of other components in the conductive material may be, for example, 20% by mass or less, 10% by mass or less, 5% by mass or less, 3% by mass or less, or 1% by mass or less, or even 0% by mass, based on the total amount of the conductive material. That is, the total amount of carbon nanotubes and carbon black in the conductive material may be, for example, 80% by mass or more, 90% by mass or more, 95% by mass or more, 97% by mass or more, or 99% by mass or more, or even 100% by mass.
[0035] The conductive material content may be, for example, 0.1% by mass or more based on the total amount of the positive electrode composition, and from the viewpoint of facilitating the development of a conductive network, it may be 0.3% by mass or more, 0.5% by mass or more, or 0.7% by mass or more. Alternatively, the conductive material content may be, for example, 10% by mass or less based on the total amount of the positive electrode composition, 7% by mass or less, 5% by mass or less, or 3% by mass or less.
[0036] <Active material> The positive electrode composition of this embodiment includes an active material. The active material can be any substance capable of reversibly intercalating and deintercalating cations. The active material can also be called the positive electrode active material.
[0037] The active material is not particularly limited; for example, known active materials used in lithium-ion secondary batteries can be used without any restrictions. Examples of active materials include lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel-manganese-cobalt oxide, and lithium iron phosphate.
[0038] For example, the active material has a volume resistivity of 1 × 10⁻⁶. 4 It may be a lithium-containing composite oxide or lithium-containing polyanionic compound containing manganese of Ω·cm or more. Examples of manganese-containing lithium-containing composite oxides include LiMnO2, LiMnO3, LiMn2O3, Li 1+x Mn 2-x Lithium manganese oxide such as O4 (where x = 0 to 0.33); LiMn x Ni y Co zO2 (x+y+z=1, 0≦y<1, 0≦z<1, 0≦x<1), Li 1+x Mn 2-x-y M y O4 (where x = 0 to 0.33, y = 0 to 1.0, 2-xy > 0), LiMn 2-x M x Examples of composite oxides containing one or more transition metal elements include O2 (where x = 0.01 to 0.1) and Li2Mn3MO8. Examples of lithium-containing polyanionic compounds include LiFePO4, LiMnPO4, and Li2MPO4F (where M is at least one metal selected from Co, Ni, Fe, Cr, and Zn). In each compositional formula, M is at least one selected from the group consisting of Fe, Co, Ni, Al, Cu, Mg, Cr, Zn, and Ta.
[0039] Average particle size of the active material (D 50 The average particle size of the active material (D) may be 20 μm or less or 10 μm or less, from the viewpoint of obtaining a battery with sufficiently good bonding between the conductive material and the binder and which has superior cycle characteristics. 50 The average particle size (D) of the active material can be measured by laser light scattering. 50 ) may be, for example, 1 μm or larger.
[0040] The active material content may be, for example, 80% by mass or more based on the total amount of the positive electrode composition, and from the viewpoint of further improving battery capacity, it may be 85% by mass or more, 90% by mass or more, or 94% by mass or more. Furthermore, the active material content may be, for example, 99.8% by mass or less based on the total amount of the positive electrode composition, 99.5% by mass or less, 99% by mass or less, 98.5% by mass or less, or 98% by mass or less. Also, the active material content may be such that the total amount of the active material and other components equals 100% by mass, and the total content of the active material, conductive material and binder (or the total content of the active material, conductive material, binder and dispersant) may be within the numerical range described later.
[0041] <Binding agent> The binder can be any material that can bond the active material and the conductive material and maintain the shape of the composite layer.
[0042] Examples of binders include polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene copolymer, and (meth)acrylic acid ester copolymer. The polymer structure of the binder may be, for example, random copolymer, alternating copolymer, graft copolymer, block copolymer, etc. From the viewpoint of excellent dielectric strength, polyvinylidene fluoride is preferred as the binder.
[0043] The binder content may be, for example, 0.5% by mass or more based on the total amount of the positive electrode composition, and may be 0.7% by mass or more, 0.8% by mass or more, 0.9% by mass or more, or 1% by mass or more from the viewpoint of better binding properties. Alternatively, the binder content may be, for example, 10% by mass or less based on the total amount of the positive electrode composition, and may be 7% by mass or less, 5% by mass or less, or 3% by mass or less from the viewpoint of further improving battery capacity. Furthermore, the binder content may be such that the total amount of the binder and other components together is 100% by mass, and the total amount of active material, conductive material and binder (or the total amount of active material, conductive material, binder and dispersant) may be within the numerical range described later.
[0044] The positive electrode composition of this embodiment may further contain a dispersant as a component other than the active material, binder, and conductive material.
[0045] <Dispersant> A dispersant is a component that assists in the dispersion of a conductive material in a liquid medium. When a positive electrode composition is manufactured using a slurry in which a conductive material and a dispersant are dispersed in a liquid medium, the positive electrode composition may contain a dispersant.
[0046] Examples of dispersants include polymeric dispersants and low molecular weight dispersants, and polymeric dispersants are preferred from the viewpoint of long-term dispersion stability of conductive materials. The dispersant may be selected from the group consisting of, for example, polyvinyl alcohol, polyvinylpyrrolidone, polyvinyl butyral, carboxymethylcellulose and its salts, polyvinyl acetal, polyvinyl acetate, polyvinylamine, and polyvinyl formal.
[0047] The dispersant content may be, for example, 100 parts by mass or less per 100 parts by mass of conductive material, and from the viewpoint of suppressing the reduction in conductivity due to the dispersant, it may be 80 parts by mass or less, 60 parts by mass or less, or 40 parts by mass or less. When the positive electrode composition of this embodiment contains a dispersant, the dispersant content may be, for example, 5 parts by mass or more per 100 parts by mass of conductive material, and from the viewpoint of further improving the dispersibility of the conductive material, it may be 10 parts by mass or more, 15 parts by mass or more, or 20 parts by mass or more.
[0048] The dispersant content may be, for example, 10% by mass or less based on the total amount of the positive electrode composition, and from the viewpoint of suppressing the decrease in conductivity due to the dispersant, it may be 5% by mass or less, 3% by mass or less, or 1% by mass or less. When the positive electrode composition of this embodiment contains a dispersant, the dispersant content may be, for example, 0.05% by mass or more based on the total amount of the positive electrode composition, and from the viewpoint of further improving the dispersibility of the conductive material, it may be 0.1% by mass or more, 0.3% by mass or more, or 0.5% by mass or more.
[0049] The positive electrode composition of this embodiment may further contain other components besides the active material, binder, conductive material, and dispersant.
[0050] Other components include, for example, humectants and defoaming agents.
[0051] The content of other components may be, for example, 5% by mass or less on a basis of the total amount of the positive electrode composition, and may also be 3% by mass or less, 2% by mass or less, 1% by mass or less, 0.5% by mass or less, 0.3% by mass or less, 0.2% by mass or less, or 0.1% by mass or less, or even 0% by mass. That is, the total content of the active material, binder and conductive material (or the total content of the active material, binder, conductive material and dispersant) may be, for example, 95% by mass or more on a basis of the total amount of the positive electrode composition, and may also be 97% by mass or more, 98% by mass or more, 99% by mass or more, 99.5% by mass or more, 99.7% by mass or more, 99.8% by mass or more, or 99.9% by mass or more, or even 100% by mass.
[0052] The positive electrode composition of this embodiment may be a material that constitutes the composite layer in the positive electrode. That is, the positive electrode composition of this embodiment may be molded in layers.
[0053] The positive electrode composition of this embodiment may be formed, for example, by applying a positive electrode forming coating solution described later and drying it.
[0054] (Coating liquid for positive electrode formation) The positive electrode forming coating liquid of this embodiment comprises an active material, a binder, a conductive material, and a liquid medium. Furthermore, the positive electrode forming coating liquid of this embodiment may further contain a dispersant.
[0055] The active material, binder, conductive material, and dispersant in the positive electrode forming coating liquid of this embodiment may be the same as the active material, binder, conductive material, and dispersant in the positive electrode composition described above. In other words, the positive electrode forming coating liquid of this embodiment can also be described as a coating liquid containing the positive electrode composition described above and a dispersion medium.
[0056] The content of active material, binder, conductive material, and dispersant in the positive electrode forming coating liquid of this embodiment (based on the total amount of solids in the positive electrode forming coating liquid) may be the same as the content of active material, binder, conductive material, and dispersant in the positive electrode composition described above (based on the total amount of the positive electrode composition).
[0057] The liquid medium can be any liquid medium capable of dispersing each component in the coating solution. Examples of liquid media include water, N-methyl-2-pyrrolidone, cyclohexane, methyl ethyl ketone, and methyl isobutyl ketone. Of these, N-methyl-2-pyrrolidone is preferred from the viewpoint of excellent dispersibility.
[0058] The content of the liquid medium is not particularly limited and should be within a range that provides sufficient coating properties for the positive electrode forming coating solution. The content of the liquid medium may be, for example, 10% by mass or more, 20% by mass or more, 30% by mass or more, or 40% by mass or more, based on the total amount of the positive electrode forming coating solution. Alternatively, the content of the liquid medium may be, for example, 90% by mass or less, 80% by mass or less, 70% by mass or less, or 60% by mass or less, based on the total amount of the positive electrode forming coating solution.
[0059] The positive electrode forming coating liquid of this embodiment can form a composite layer composed of the above-described positive electrode composition by application and drying. Here, drying refers to the operation of removing at least a portion of the liquid medium from the coating film obtained by applying the positive electrode forming coating liquid.
[0060] The method for applying the coating solution for forming the positive electrode in this embodiment is not particularly limited and may be appropriately selected from known coating methods (coating means, coating apparatus). Examples of coating methods include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic coating.
[0061] The drying method for the coating film is not particularly limited and may be appropriately selected from known drying methods (drying means, drying apparatus). Examples of drying methods include vaporizing at least a portion of the dispersion medium by heating and / or reducing pressure. Drying methods may include, for example, drying by standing, heating, or reduced pressure drying, and may also be drying methods using dryers such as forced-air dryers, hot-air dryers, infrared heaters, or far-infrared heaters.
[0062] The positive electrode forming coating liquid of this embodiment may be applied, for example, to a current collector and dried. This forms a composite layer made of the positive electrode composition on the current collector, and a positive electrode including the current collector and the composite layer is obtained.
[0063] The positive electrode forming coating liquid of this embodiment can be obtained by dispersing each component of the positive electrode composition described above in a liquid medium. The positive electrode forming coating liquid of this embodiment may be manufactured, for example, by the following manufacturing method.
[0064] <Method for manufacturing a coating solution for forming a positive electrode> A method for producing a coating liquid for forming a positive electrode may include, for example, a step of mixing each component of the positive electrode composition described above with a liquid medium. This step may be a step of dispersing each component in the liquid medium at once, or it may be a step of dispersing each component separately in the liquid medium and then mixing them.
[0065] A method for producing a coating liquid for forming a positive electrode may include a first step of mixing carbon nanotube powder with a liquid medium to obtain a first slurry containing carbon nanotubes; a second step of mixing carbon black, a binder, an active material, and a liquid medium to obtain a mixed liquid; and a third step of mixing the first slurry with the mixed liquid to obtain a coating liquid for forming a positive electrode.
[0066] In the above manufacturing method, in the first step, carbon nanotubes are pre-formed into a slurry to have a predetermined average length; in the second step, components other than carbon nanotubes are pre-mixed to form a mixed liquid; and in the third step, the carbon nanotubes are mixed with the mixed liquid in a slurry state. Therefore, in the above manufacturing method, during the mixing in the third step, the carbon nanotubes and other components (e.g., carbon black, active material, binder, etc.) are mixed with low stress, so the crushing of the carbon nanotubes is sufficiently suppressed, and a coating liquid for cathode formation containing carbon nanotubes having a predetermined average length can be easily manufactured.
[0067] The first step may be a step of mixing carbon nanotube powder and a liquid medium while crushing at least a portion of the carbon nanotube powder to obtain a first slurry containing the carbon nanotubes described above.
[0068] It is also conceivable to prepare carbon nanotube powder having the above-mentioned average length in advance and mix this carbon nanotube powder with other components to prepare the coating solution for cathode formation. However, since carbon nanotube powder contains many bundled carbon nanotubes, this method tends to form aggregates when dispersed in a liquid medium, making it difficult to form a suitable dispersion state. In contrast, in the first step described above, the carbon nanotubes are deliberately crushed when the carbon nanotube powder and liquid medium are mixed, and their average length is brought within the above-mentioned range, thereby easily preparing a slurry in which carbon nanotubes having a predetermined average length are dispersed in a suitable dispersion state.
[0069] The mixing method in the first step is not particularly limited and may be appropriately selected from known mixing methods (mixing means, mixing apparatus) (for example, stirring and mixing using a ball mill, sand mill, twin-screw kneader, rotary-orbit agitator, planetary mixer, disper mixer, etc.).
[0070] The mixing conditions in the first step are not particularly limited and may be adjusted as appropriate so that the average length of the carbon nanotubes in the first slurry falls within the above range.
[0071] The average length of the carbon nanotube powder is preferably shorter than the average length of the carbon nanotubes in the first slurry. The average length of the carbon nanotube powder may be, for example, 10 μm or more, 20 μm or more, 30 μm or more, or 40 μm or more. Alternatively, the average length of the carbon nanotube powder may be, for example, 1000 μm or less, or 100 μm or less.
[0072] In this specification, the average length of carbon nanotube powder is measured by the following method. The average length of carbon nanotubes is calculated based on images obtained by observing them with a scanning electron microscope (SEM). Specifically, using a field emission scanning electron microscope Regulus8220 (manufactured by Hitachi High-Tech Corporation), 10 images of carbon nanotubes are taken at a magnification of 2000x. The lengths of 100 randomly selected carbon nanotubes from the resulting images are measured by image analysis, and the average length is obtained by arithmetic mean.
[0073] The average diameter and peak ratio (D / G) in carbon nanotube powder may be the same as those for carbon nanotubes described above.
[0074] The carbon nanotube content in the first slurry may be, for example, 0.1% by mass or more, or 1% by mass or more, 2% by mass or more, or 3% by mass or more, based on the total amount of the first slurry. Alternatively, the carbon nanotube content in the first slurry may be, for example, 40% by mass or less, or 30% by mass or less, 20% by mass or less, or 10% by mass or less, based on the total amount of the first slurry.
[0075] Examples of liquid media in the first slurry include those described above.
[0076] The content of the liquid medium in the first slurry is not particularly limited and should be an amount sufficient to adequately disperse the carbon nanotubes. The content of the liquid medium in the first slurry may be, for example, an amount such that the solid content concentration of the first slurry falls within the numerical range described below.
[0077] In the first step, a dispersant may be further mixed in.
[0078] When the first slurry contains a dispersant, the amount of dispersant may be, for example, 5 parts by mass or more, 10 parts by mass or more, 15 parts by mass or more, or 20 parts by mass or more, per 100 parts by mass of carbon nanotubes. Alternatively, the amount of dispersant in the first slurry may be, for example, 100 parts by mass or less, 90 parts by mass or less, 80 parts by mass or less, or 70 parts by mass or less, per 100 parts by mass of carbon nanotubes.
[0079] The first slurry may further contain other components besides carbon nanotubes, a dispersant, and a liquid medium. Examples of other components include carbon black, graphite, a binder, a wetting agent, and so on.
[0080] The content of other components in the first slurry may be, for example, 5% by mass or less on a basis of the total amount of solids in the first slurry, and may also be 3% by mass or less, 2% by mass or less, 1% by mass or less, 0.5% by mass or less, 0.3% by mass or less, 0.2% by mass or less, or 0.1% by mass or less, or even 0% by mass. That is, the total content of carbon nanotubes and dispersants in the first slurry may be, for example, 95% by mass or more on a basis of the total amount of solids in the first slurry, and may also be 97% by mass or more, 98% by mass or more, 99% by mass or more, 99% by mass or more, 99.5% by mass or more, 99.7% by mass or more, 99.8% by mass or more, or 99.9% by mass or more, or even 100% by mass.
[0081] The solid content concentration of the first slurry may be, for example, 0.1% by mass or more, and may be 1% by mass or more, 2% by mass or more, or 3% by mass or more. Alternatively, the solid content concentration of the first slurry may be, for example, 40% by mass or less, and may be 30% by mass or less, 20% by mass or less, or 10% by mass or less.
[0082] The second step is to mix carbon black, a binder, an active material, and a liquid medium. This second step yields a mixture containing carbon black, a binder, an active material, and a liquid medium.
[0083] The second step may be, for example, a step of mixing a second slurry containing carbon black, a binder solution containing a binder, and an active material.
[0084] The second slurry contains carbon black and a liquid medium, and may further contain a dispersant. Examples of carbon black, dispersant, and liquid medium are the same as those described above.
[0085] The carbon black content in the second slurry may be, for example, 0.1% by mass or more, or 1% by mass or more, 2% by mass or more, or 3% by mass or more, based on the total amount of the second slurry. Alternatively, the carbon black content in the second slurry may be, for example, 40% by mass or less, or 30% by mass or less, 20% by mass or less, or 10% by mass or less, based on the total amount of the second slurry.
[0086] The content of the liquid medium in the second slurry is not particularly limited, and should be an amount sufficient to adequately disperse the carbon black. The content of the liquid medium in the second slurry may be, for example, an amount such that the solid content concentration of the second slurry falls within the numerical range described below.
[0087] When the second slurry contains a dispersant, the amount of dispersant may be, for example, 1 part by mass or more, 3 parts by mass or more, 5 parts by mass or more, or 7 parts by mass or more, per 100 parts by mass of carbon black. Alternatively, the amount of dispersant in the second slurry may be, for example, 100 parts by mass or less, per 100 parts by mass of carbon black, 70 parts by mass or less, 50 parts by mass or less, 30 parts by mass or less, or 20 parts by mass or less.
[0088] The second slurry may further contain other components besides carbon black, a dispersant, and a liquid medium. Examples of other components include carbon nanotubes, graphite, binders, and wetting agents.
[0089] The content of other components in the second slurry may be, for example, 5% by mass or less based on the total amount of solids in the second slurry, and may also be 3% by mass or less, 2% by mass or less, 1% by mass or less, 0.5% by mass or less, 0.3% by mass or less, 0.2% by mass or less, or 0.1% by mass or less, or even 0% by mass. That is, the total content of carbon black and dispersant in the second slurry may be, for example, 95% by mass or more based on the total amount of solids in the second slurry, and may also be 97% by mass or more, 98% by mass or more, 99% by mass or more, 99% by mass or more, 99.5% by mass or more, 99.7% by mass or more, 99.8% by mass or more, or 99.9% by mass or more, or even 100% by mass.
[0090] The solid content concentration of the second slurry may be, for example, 0.1% by mass or more, and may be 1% by mass or more, 2% by mass or more, or 3% by mass or more. Alternatively, the solid content concentration of the second slurry may be, for example, 40% by mass or less, and may be 30% by mass or less, 20% by mass or less, or 15% by mass or less.
[0091] The binder solution contains a binder and a liquid medium. Examples of the binder and liquid medium are the same as those described above.
[0092] The binder content in the binder solution may be, for example, 0.1% by mass or more on a total basis of the binder solution, and may also be 1% by mass or more, 2% by mass or more, or 3% by mass or more. Alternatively, the binder content in the binder solution may be, for example, 40% by mass or less on a total basis of the binder solution, and may also be 30% by mass or less, 20% by mass or less, or 10% by mass or less.
[0093] The amount of liquid medium in the binder solution is not particularly limited and should be sufficient to adequately dissolve the binder. For example, the amount of liquid medium in the binder solution may be such that the solid content concentration of the binder solution falls within the range of values described below.
[0094] The binder solution may further contain other components besides the binder and the liquid medium. Examples of other components include carbon black, carbon nanotubes, graphite, and wetting agents.
[0095] The content of other components in the binder solution may be, for example, 5% by mass or less based on the total amount of solids in the binder solution, and may also be 3% by mass or less, 2% by mass or less, 1% by mass or less, 0.5% by mass or less, 0.3% by mass or less, 0.2% by mass or less, or 0.1% by mass or less, or even 0% by mass. That is, the content of the binder in the binder solution may be, for example, 95% by mass or more based on the total amount of solids in the binder solution, and may also be 97% by mass or more, 98% by mass or more, 99% by mass or more, 99% by mass or more, 99.5% by mass or more, 99.7% by mass or more, 99.8% by mass or more, or 99.9% by mass or more, or even 100% by mass.
[0096] The solid content concentration of the binder solution may be, for example, 0.1% by mass or more, and may be 1% by mass or more, 2% by mass or more, or 3% by mass or more. Alternatively, the solid content concentration of the binder solution may be, for example, 40% by mass or less, and may be 30% by mass or less, 20% by mass or less, or 10% by mass or less.
[0097] In the second step, the liquid medium may be mixed as a component in the second slurry and binder solution. Alternatively, in the second step, the liquid medium may be further mixed separately from the second slurry and binder solution. The amount of liquid medium is not particularly limited and may be adjusted as appropriate so that the viscosity of the mixture is such that it can be mixed with the first slurry. The amount of liquid medium may also be adjusted as appropriate so that the solid content concentration of the cathode forming coating solution after mixing the first slurry and the mixture is within the range described above.
[0098] The mixing method in the second step is not particularly limited and may be appropriately selected from known mixing methods (mixing means, mixing apparatus) (for example, stirring and mixing using a ball mill, sand mill, twin-screw kneader, rotary-orbit agitator, planetary mixer, disper mixer, etc.).
[0099] The mixing conditions for the second step are not particularly limited; any conditions that allow the components to be sufficiently dispersed and produce a mixture with sufficient viscosity to be mixed with the first slurry are acceptable.
[0100] The viscosity of the mixture may be, for example, 5000 mPa·s or less, or 3000 mPa·s or less. Alternatively, the viscosity of the mixture may be, for example, 500 mPa·s or more, or 700 mPa·s or more.
[0101] In this specification, the viscosity of the mixture is expressed as a value measured by the following method. The viscosity of the obtained mixture was evaluated using a rotary rheometer as described in JIS K7244-10. Specifically, using a rotary rheometer (Anton Paar, MCR302), 1 g of the mixture was applied to a disk at 25°C, and the shear rate was set to 0.01 sec. -1 from 100 seconds -1 Measurements were taken while varying the shear rate up to 10 seconds. -1 The viscosity was calculated.
[0102] The third step is to mix the first slurry with the mixed liquid. This third step yields a coating solution for forming a positive electrode containing conductive materials (carbon nanotubes and carbon black), a binder, an active material, and a liquid medium.
[0103] The third step makes it easy to obtain a uniform cathode-forming coating while sufficiently suppressing the crushing of carbon nanotubes in the first slurry (i.e., while maintaining the average length of the carbon nanotubes within a predetermined range).
[0104] In the third step, the liquid medium may be further mixed. The amount of the liquid medium is not particularly limited and may be adjusted as appropriate so that the viscosity of the coating solution for forming the positive electrode can be applied. The amount of the liquid medium may also be adjusted as appropriate so that the solid content concentration of the coating solution for forming the positive electrode is within the range described above.
[0105] The mixing method in the third step is not particularly limited and may be appropriately selected from known mixing methods (mixing means, mixing apparatus) (for example, stirring and mixing using a ball mill, sand mill, twin-screw kneader, rotary-orbit agitator, planetary mixer, disper mixer, etc.).
[0106] The mixing conditions in the third step are not particularly limited, and any conditions that allow for sufficient dispersion of each component and yield a cathode-forming coating solution with a suitable viscosity are acceptable. In the third step, carbon nanotubes are mixed with other components in a slurry state, so during mixing in the third step, the carbon nanotubes and other components (e.g., active material, binder, etc.) are mixed under small stress, which is thought to sufficiently suppress the crushing of the carbon nanotubes. The third step may be a step to obtain a cathode-forming coating solution containing an active material, a binder, carbon black, and carbon nanotubes with an average length of 0.4 μm or more and 8 μm or less.
[0107] The mixing conditions for the third step are not particularly limited; any conditions that allow the components to be sufficiently dispersed and produce a coating solution for forming a positive electrode with a suitable viscosity for application are acceptable.
[0108] The third step may be, for example, a step of mixing the first slurry with a mixed liquid to obtain a coating liquid for forming a positive electrode containing an active material, a binder, carbon black, and carbon nanotubes having an average length of 0.4 μm or more and 8 μm or less.
[0109] (positive electrode) The positive electrode of this embodiment includes the positive electrode composition described above. The positive electrode of this embodiment may include, for example, a composite layer made of the positive electrode composition and a current collector. The composite layer may be arranged (laminated) on the current collector.
[0110] The current collector is not particularly limited, and known current collectors can be used without any particular restrictions. Examples of current collectors include metal foil (metals such as gold, silver, copper, platinum, aluminum, iron, nickel, chromium, manganese, lead, tungsten, and titanium, as well as alloys mainly composed of any one of these). Current collectors are generally provided in the form of foil, but are not limited to this, and perforated foil and mesh-type current collectors can also be used.
[0111] The composite layer may contain the above-described positive electrode composition, or may be composed of the above-described positive electrode composition.
[0112] The thickness of the composite layer may be, for example, 20 μm or more, and from the viewpoint of further improving conductivity, it may be 30 μm or more, 40 μm or more, or 50 μm or more. Alternatively, the thickness of the composite layer may be, for example, 100 μm or less, and from the viewpoint of further improving conductivity, it may be 90 μm or less, 80 μm or less, or 70 μm or less.
[0113] The positive electrode of this embodiment may be manufactured by a manufacturing method (a method for manufacturing a positive electrode) that includes a composite layer formation step, in which the above-mentioned positive electrode forming coating liquid is applied to a current collector and dried to form a composite layer on the current collector.
[0114] The method for manufacturing the positive electrode may further include a pressurizing step in which the composite layer formed in the composite layer formation step and the current collector are pressed in the stacking direction. The pressurizing method in the pressurizing step is not particularly limited and may be, for example, a roll press, a die press, a calender press, or the like.
[0115] The method for manufacturing the positive electrode may further include a drying step to remove moisture from the composite layer after the pressurization step. In the drying step, residual moisture in the composite layer may be removed, for example, by vacuum drying.
[0116] The positive electrode of this embodiment can be suitably used as the positive electrode of a battery, particularly a secondary battery (e.g., a lithium-ion secondary battery).
[0117] (battery) The battery of this embodiment is equipped with the positive electrode described above. The battery of this embodiment may be a secondary battery, or it may be a lithium-ion secondary battery. Because the battery of this embodiment is equipped with the positive electrode described above, it tends to have excellent cycle characteristics.
[0118] In the battery of this embodiment, the components other than the positive electrode may be the same as those of known batteries. The method for manufacturing the battery of this embodiment is also not particularly limited, and it can be manufactured in the same way as known battery manufacturing methods, except that the positive electrode described above is used.
[0119] The battery of this embodiment may, for example, include the positive electrode, negative electrode, and separator described above.
[0120] The separator is not particularly limited, and any separator known as a separator for lithium-ion secondary batteries can be used without any particular restriction. Examples of separators include synthetic resins such as polyethylene and polypropylene. The separator is preferably a porous film because it has good electrolyte retention properties.
[0121] The negative electrode is not particularly limited, and any negative electrode known as a negative electrode for lithium-ion secondary batteries can be used without any particular restriction. The negative electrode may, for example, comprise a negative electrode composite layer containing a negative electrode active material and a binder, and a negative electrode current collector.
[0122] The battery of this embodiment may, for example, include an electrode group in which a positive electrode and a negative electrode are stacked or wound together with a separator in between.
[0123] In this embodiment, the battery may, for example, have a positive electrode, a negative electrode, and a separator immersed in an electrolyte.
[0124] The electrolyte is not particularly limited and may be, for example, a non-aqueous electrolyte containing a lithium salt. Examples of non-aqueous solvents in a non-aqueous electrolyte containing a lithium salt include ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, and methyl ethyl carbonate. Examples of lithium salts that can be dissolved in a non-aqueous solvent include lithium hexafluoride phosphate, lithium borotetrafluoride, and lithium trifluoromethanesulfonate. Furthermore, the battery of this embodiment may use an ion-conducting polymer or the like as the electrolyte.
[0125] The battery of this embodiment is not particularly limited in its applications and can be used in a wide range of fields, such as portable AV equipment including digital cameras, video cameras, portable audio players, portable LCD TVs, portable information terminals such as notebook computers, smartphones, and mobile PCs, as well as portable game devices, power tools, electric bicycles, hybrid vehicles, electric vehicles, and power storage systems.
[0126] While preferred embodiments of this disclosure have been described above, this disclosure is not limited to the embodiments described above.
[0127] (slurry) One aspect of this disclosure relates, for example, to a slurry comprising carbon nanotubes and a liquid medium. The slurry may further contain a dispersant. In the slurry, the average length of the carbon nanotubes is 0.4 μm or more and 8 μm or less.
[0128] The slurry mentioned above may be the same as the first slurry described above.
[0129] The slurry described above can be used, for example, in the manufacture of the coating liquid for forming the positive electrode. It can also be used for applications such as a coating liquid for forming the negative electrode or a coating liquid for carbon-coated current collectors.
[0130] (Methods for evaluating and sorting slurries) Another aspect of this disclosure may be a method for evaluating a slurry, which includes, for example, a preparation step of preparing a slurry containing carbon nanotubes and a liquid medium, and an evaluation step of measuring the average length of the carbon nanotubes in the slurry and evaluating the slurry based on the average length.
[0131] Another aspect of this disclosure may be a method for sorting a slurry, for example, comprising a preparation step of preparing a slurry containing carbon nanotubes and a liquid medium, and a sorting step of measuring the average length of the carbon nanotubes in the slurry and sorting the slurry based on the average length.
[0132] The sorting step may be, for example, a step of sorting slurries in which the average length of carbon nanotubes in the slurry is within the above-mentioned range.
[0133] The above evaluation method and sorting method may further include a step of mixing carbon nanotube powder with a liquid medium to obtain a slurry containing carbon nanotubes.
[0134] (Methods for evaluating slurry manufacturing conditions, sorting methods) Another aspect of this disclosure may be, for example, a method for evaluating slurry manufacturing conditions, which includes a mixing step of mixing carbon nanotube powder and a liquid medium to obtain a slurry containing carbon nanotubes, and an evaluation step of measuring the average length of carbon nanotubes in the slurry obtained in the mixing step and evaluating the slurry manufacturing conditions in the mixing step based on the average length.
[0135] Another aspect of this disclosure may be a method for selecting slurry manufacturing conditions, which includes, for example, a mixing step of mixing carbon nanotube powder and a liquid medium to obtain a slurry containing carbon nanotubes, and a selection step of measuring the average length of carbon nanotubes in the slurry obtained in the mixing step and selecting the slurry manufacturing conditions in the mixing step based on the average length.
[0136] The sorting step may be, for example, a step of selecting manufacturing conditions for a slurry in which the average length of carbon nanotubes in the slurry falls within the above-mentioned range.
[0137] Another aspect of this disclosure may be a method for producing a slurry, which includes a step of producing a slurry under the manufacturing conditions selected by the selection method described above. [Examples]
[0138] The following describes in more detail an aspect of this disclosure by reference to examples, but this disclosure is not limited to these examples.
[0139] (Example 1) (1) Preparation of CNT slurry (carbon nanotube slurry) Carbon nanotubes (CNano, "Flotube6000", average diameter 6 nm, average length 70 μm), N-methyl-2-pyrrolidone (hereinafter referred to as NMP) as a dispersion medium, and polyvinyl alcohol (Denka, POVAL B05) as a dispersant were prepared. 1% by mass of polyvinyl alcohol and 4% by mass of carbon nanotubes were added to 95% by mass of NMP and stirred for 120 minutes in a planetary mixer (Primix, Hibis Disperser Mix 3D-5) to obtain a slurry. Next, the obtained slurry was placed in a bead mill (Ashizawa Finetech, Mugen Flow MGF2-ZA) equipped with zirconia beads (diameter 0.5 mm) and dispersed for 20 minutes. After dispersion, the zirconia beads were removed by filtration to prepare a carbon nanotube slurry. The average length of the carbon nanotubes in the obtained CNT slurry was 5 μm.
[0140] (2) Preparation of CB slurry (carbon black slurry) Carbon black (Denka Co., Ltd., "Li-500"), N-methyl-2-pyrrolidone (hereinafter referred to as NMP) as a dispersion medium, and polyvinyl alcohol (Denka Co., Ltd., Poval B05) as a dispersant were prepared. 1.0% by mass of polyvinyl alcohol and 10.0% by mass of carbon black were added to 89.0% by mass of NMP and stirred for 120 minutes in a planetary mixer (Primix Co., Ltd., Hibis Dispers Mix 3D-5 type) to obtain a slurry. Next, the obtained slurry was placed into a bead mill (Ashizawa Finetech Co., Ltd., Mugen Flow MGF2-ZA) equipped with zirconia beads (diameter 0.5 mm) and dispersed. After dispersion, the zirconia beads were removed by filtration to prepare a carbon black slurry.
[0141] (3) Preparation of coating solution for positive electrode formation CNT slurry and CB slurry were prepared using the method described above. Additionally, the active material had an average particle size of D 50 Lithium nickel-manganese cobalt oxide (ME6E), manufactured by Beijing Dangsheng Co., Ltd., was prepared as 10 μm particles, an NMP solution of polyvinylidene fluoride (Solef5130), manufactured by Solvey, Inc., was prepared as a binder, and NMP was prepared as a dispersion medium. The amounts of each raw material were adjusted so that the active material was 97.55 mass%, the conductive material was 1.0 mass (0.3 mass%, carbon black was 0.7 mass%), the binder was 1.3 mass%, and the dispersant was 0.15 mass%, in terms of solid ratio. First, the CB slurry, the NMP solution of polyvinylidene fluoride, and the active material were mixed, then the CNT slurry was further mixed, and NMP was added and mixed further until a coating viscosity was achieved to obtain a coating solution for cathode formation. Mixing was performed using a rotation-and-revolution type mixer (ARV-310, manufactured by Thinky Co., Ltd.).
[0142] (4) Manufacturing of the positive electrode The coating solution for forming the positive electrode prepared in (3) above was deposited onto one side of a 15 μm thick aluminum foil (manufactured by UACJ) using an applicator to create a laminate, which was then left to stand in a dryer and pre-dried at 105°C for 1 hour to completely remove NMP. Next, the dried laminate was pressed in a roll press machine at a linear pressure of 200 kg / cm so that the total thickness of the laminate was 80 μm. Then, it was vacuum dried at 170°C for 3 hours to completely remove residual moisture, and a positive electrode comprising a current collector and an asphalt layer was obtained.
[0143] (5) Manufacturing of the negative electrode Pure water (manufactured by Kanto Chemical Co., Ltd.) was prepared as the solvent, artificial graphite (manufactured by Hitachi Chemical Co., Ltd., "MAG-D") as the negative electrode active material, styrene-butadiene rubber (manufactured by Nippon Zeon Co., Ltd., "BM-400B", hereinafter referred to as SBR) as the binder, and carboxymethylcellulose (manufactured by Daicel Corporation, "D2200", hereinafter referred to as CMC) as the dispersant. Next, CMC was weighed to 1% by mass in solid content and artificial graphite to 97% by mass in solid content and mixed. Pure water was added to this mixture and mixed until homogeneous using a rotation-and-revolution type mixer (manufactured by Thinky Co., Ltd., Awatori Rentaro ARV-310) to obtain a mixture. Next, SBR was weighed to 2% by mass in solid content and added to the obtained mixture and mixed until homogeneous using a rotation-and-revolution type mixer (manufactured by Thinky Co., Ltd., Awatori Rentaro ARV-310) to obtain a coating liquid for negative electrode formation. Next, a coating solution for forming the negative electrode was applied to a 10 μm thick copper foil (manufactured by UACJ) using an applicator to create a laminate, which was then left to stand in a dryer and pre-dried at 60°C for 1 hour. Next, the laminate was pressed with a roll press at a linear pressure of 50 kg / cm so that the total thickness of the laminate was 60 μm. Finally, it was vacuum-dried at 120°C for 3 hours to completely remove any residual moisture, and a negative electrode comprising a current collector and an asphalt layer was obtained.
[0144] (5) Battery manufacturing In a dry room controlled to a dew point of -50°C or lower, the positive electrode was processed to 40 x 40 mm and the negative electrode to 44 x 44 mm. Then, an aluminum tab was welded to the positive electrode and a nickel tab to the negative electrode. The composite coating surfaces of the positive and negative electrodes were positioned facing each other in the center, and a 45 x 45 mm polyolefin microporous membrane was placed between the positive and negative electrodes. Next, a sheet-like outer covering cut and processed to a 70 x 140 mm square was folded in half along the center of its long side. Then, the outer covering was positioned so that the aluminum tab for the positive electrode and the nickel tab for the negative electrode were exposed to the outside of the outer covering, and the laminate of the positive electrode / polyolefin microporous membrane / negative electrode was sandwiched between the folded outer covering. Next, using a heat sealer, two sides of the outer casing, including the side where the aluminum tab for the positive electrode and the nickel tab for the negative electrode are exposed, were heat-fused together. Then, 2 g of electrolyte (a solution containing ethylene carbonate / diethyl carbonate = 1 / 2 (volume ratio) and 1 M LiPF6 solution, manufactured by Kishida Chemical Co., Ltd.) was poured into the unfused side to allow the electrolyte to thoroughly permeate the positive electrode, negative electrode, and polyolefin microporous membrane. Finally, the remaining side of the outer casing was heat-fused together using a vacuum heat sealer while reducing the internal pressure to obtain a lithium-ion secondary battery.
[0145] (6) Battery evaluation (6-1) Evaluation of internal resistance The fabricated battery was charged at 25°C under constant current and voltage conditions, limited to 4.3V and 0.2C, and then discharged to 3.0V under a constant current of 0.2C. Next, it underwent 5 charge / discharge cycles under the same conditions, and then charged to a depth of charge of 50%. Afterward, impedance measurements were performed at a frequency range of 1.5MHz to 0.01Hz and an oscillating voltage of 5mV to determine the internal resistance. The results are shown in Table 1.
[0146] (6-2) Evaluation of cycle characteristics The fabricated batteries were charged at 25°C with a constant current and voltage limit of 4.3V and 1C, and then discharged to 3.0V with a constant current of 1C. The above charge-discharge cycle was repeated 500 times, and the discharge capacity in each cycle was measured. As an indicator of the battery's cycle characteristics, the cycle capacity retention rate was calculated as the capacity retention rate after 500 cycles relative to the capacity retention rate after 1 cycle. The results are shown in Table 1.
[0147] (Example 2) In (1) above, a CNT slurry was obtained in the same manner as in Example 1, except that the dispersion processing time in the bead mill was changed to 30 minutes. The average length of carbon nanotubes in the obtained CNT slurry was 3 μm. Using the obtained CNT slurry, the preparation of the coating solution for cathode formation, the manufacture of the cathode, the manufacture of the battery, and the evaluation of the battery were carried out in the same manner as in Example 1. The results are shown in Table 1.
[0148] (Example 3) In (1) above, a CNT slurry was obtained in the same manner as in Example 1, except that the dispersion processing time in the bead mill was changed to 40 minutes. The average length of the carbon nanotubes in the obtained CNT slurry was 2 μm. Using the obtained CNT slurry, the preparation of the coating solution for cathode formation, the manufacture of the cathode, the manufacture of the battery, and the evaluation of the battery were carried out in the same manner as in Example 1. The results are shown in Table 1.
[0149] (Example 4) In (1) above, a CNT slurry was obtained in the same manner as in Example 1, except that the dispersion processing time in the bead mill was changed to 60 minutes. The average length of the carbon nanotubes in the obtained CNT slurry was 1 μm. Using the obtained CNT slurry, the preparation of the coating solution for cathode formation, the manufacture of the cathode, the manufacture of the battery, and the evaluation of the battery were carried out in the same manner as in Example 1. The results are shown in Table 1.
[0150] (Example 5) In (1) above, a CNT slurry was obtained in the same manner as in Example 1, except that the dispersion processing time in the bead mill was changed to 90 minutes. The average length of carbon nanotubes in the obtained CNT slurry was 0.5 μm. Using the obtained CNT slurry, the preparation of the coating solution for cathode formation, the manufacture of the cathode, the manufacture of the battery, and the evaluation of the battery were carried out in the same manner as in Example 1. The results are shown in Table 1.
[0151] (Comparative Example 1) In (1) above, a CNT slurry was obtained in the same manner as in Example 1, except that the dispersion processing time in the bead mill was changed to 10 minutes. The average length of the carbon nanotubes in the obtained CNT slurry was 10 μm. Using the obtained CNT slurry, the preparation of the coating solution for cathode formation, the manufacture of the cathode, the manufacture of the battery, and the evaluation of the battery were carried out in the same manner as in Example 1. The results are shown in Table 1.
[0152] (Comparative Example 2) In (1) above, a CNT slurry was obtained in the same manner as in Example 1, except that the dispersion processing time in the bead mill was changed to 120 minutes. The average length of carbon nanotubes in the obtained CNT slurry was 0.3 μm. Using the obtained CNT slurry, the preparation of the coating solution for cathode formation, the manufacture of the cathode, the manufacture of the battery, and the evaluation of the battery were carried out in the same manner as in Example 1. The results are shown in Table 1.
[0153] [Table 1]
Claims
1. It comprises an active material, a binder, and a conductive material. The conductive material contains carbon black and carbon nanotubes, A positive electrode composition in which the average length of the carbon nanotubes is 0.4 μm or more and 8 μm or less.
2. The positive electrode composition according to claim 1, wherein the average diameter of the carbon nanotubes is 1 nm or more and 15 nm or less.
3. The positive electrode composition according to claim 1, wherein the carbon nanotube content is 10% by mass or more and 70% by mass or less based on the total amount of the conductive material.
4. A positive electrode comprising a composite layer made of the positive electrode composition according to any one of claims 1 to 3.
5. A battery comprising the positive electrode described in claim 4.
6. It comprises an active material, a binder, a conductive material, and a liquid medium. The conductive material contains carbon black and carbon nanotubes, A coating liquid for forming a positive electrode, wherein the average length of the carbon nanotubes is 0.4 μm or more and 8 μm or less.
7. A first step involves mixing carbon nanotube powder with a liquid medium to obtain a first slurry containing carbon nanotubes, The second step involves mixing carbon black, a binder, an active material, and a liquid medium to obtain a mixed solution. A third step involves mixing the first slurry and the mixed liquid to obtain a coating liquid for forming a positive electrode containing the carbon nanotubes, the carbon black, the binder, the active material, and the liquid medium. Includes, A method for producing a coating liquid for forming a positive electrode, wherein the first step is to mix the carbon nanotube powder and the liquid medium such that the average length of the carbon nanotubes in the first slurry is 0.4 μm or more and 8 μm or less.
8. The manufacturing method according to claim 7, wherein the second step is a step of mixing the second slurry containing the carbon black, the binder solution containing the binder, and the active material.
9. A method for manufacturing a positive electrode, comprising a step of forming an asphalt layer by applying the positive electrode forming coating liquid described in claim 6, or a positive electrode forming coating liquid manufactured by the manufacturing method described in claim 7, onto a current collector to form an asphalt layer on the current collector.
10. A process of forming a composite layer on a current collector by applying the positive electrode forming coating liquid described in claim 6, or a positive electrode forming coating liquid manufactured by the manufacturing method described in claim 7, to the current collector, A battery formation step involves stacking the positive electrode and the negative electrode with a separator in between to obtain a battery, A method for manufacturing batteries, including the invention of a battery.
Citation Information
Patent Citations
Conductive slurry, electrode slurry and electrode for electric double-layer capacitor using the slurry
JP2008227481A